Message Framing Effects on Individuals' Social Distancing and Helping Behavior During the COVID-19 Pandemic - Ceylan, Melis; Hayran, Ceren (Frontiers in Psychology, 2021)
This research responds to urgent calls to fill knowledge gaps on COVID-19 in communicating social distancing messages to the public in the most convincing ways. The authors explore the effectiveness of framing social distancing messages around prosocial versus self-interested appeals in driving message compliance and helping behavior. The results show that when a message emphasizes benefits for everyone in society, rather than solely for the individual, citizens find the message more persuasive to engage in social distancing, and also more motivating to help others. Results further demonstrate that the proposed effects are higher for individuals who have lower locus of control and lower fear of coronavirus as prosocial messages lead them to feel a joint responsibility in protecting from the pandemic. Theoretical and practical implications of the results are discussed.